New species of Adeonellopsis (Bryozoa: Adeonidae) from southern Zealandia and the western Tasman Sea - Liow, Lee Hsiang; Gordon, Dennis P. (Zootaxa, 2020)
Seven new species of Adeonellopsis MacGillivray, 1886 are described: Adeonellopsis macewindui, A. gracilis (endemic to New Zealand), A. gemina (New Zealand and Norfolk Island shelf), A. tasmanensis (Norfolk Island shelf and Gascoyne Seamount), A. periculosa Norfolk Island shelf) and A. wassi and A. minor (New South Wales shelf). All have flattened staghorn branches, which range in width from 0.8 to 5 mm, depending on species. Based on underwater photos, the largest species, A. macewindui n. sp. forms locally significant habitat on fiord walls and parts of the continental shelf in New Zealand, sometimes in association with A. gemina n. sp.. The latter can survive as isolated fragments that can regenerate from broken ends. Three species have a number of large gonozooids at selected locations on their branches and two of these species have vestigial ooecia in their gonozooids, recorded for the first time in Adeonidae. The remaining four species have among their autozooids only a few zooids that are a little larger, with larger compound spiramina. These are suggested to function as gonozooids, representing the larger end of a size spectrum for reproductive zooids, of which those at the lower end are the same size as autozooids. The encrusting Australian species known as Adeonellopsis baccata (Hutton, 1878) is transferred to Reptadeonella as Reptadeonella baccata n. comb..